Penerapan Pemberian Minyak Zaitun pada Asuhan Keperawatan Anak Dengan Gastroenteritis - Ivony Asih Munte; IGA Dewi Purnamawati (AKPER Pasar Rebo, 2023)
Background: Gastroenteritis is an infectious disease which is one of the causes of death in children. The problems caused also vary, not only disturbing the gastrointestinal system but also the integumentary system, namely the appearance of diaper rash due to an increase in the frequency of bowel movements due to frequent use of diapers. Diaper rash often occurs in children with gastroenteritis, the cause of which is skin contact with irritants in the genital area in the form of a reddish rash that causes discomfort to the child. The application of olive oil can reduce and prevent irritation in the child's genital area. Purpose: this study aims to prevent and reduce diaper rash in children with skin integrity disorders by administering olive oil. Method: descriptive research using a case study approach and literature as well as the application of Evidence-Based Nursing to an 11-month-old boy with gastroenteritis. Evidence Based Nursing is by applying olive oil to the baby's genital area for three days and given twice a day. Results: the problem of impaired skin integrity in children decreased where there was a decrease in the degree of diaper rash from moderate to mild. Conclusion: giving olive oil can prevent and reduce irritation to the baby's genital skin due to the frequent use of diapers due to diarrhea.